Pengaruh Penerapan E-system Perpajakan Terhadap Tingkat Kepatuhan Wajib Pajak Orang Pribadi - Ersania, Gusti Ayu Raisa; Merkusiwati, Ni Ketut Lely Aryani (E-Jurnal Akuntansi, 2018)
This study aims to determine the effect of e-System application of taxation on the level of taxpayer compliance of individuals at the Tax Office Pratama East Denpasar. The sample in this research is 100 individual taxpayers active and registered in KPP Pratama East Denpasar. One method used to determine the number of samples is to use the Slovin formula. Data analysis method used is multiple linear regression. This type of research is primary data obtained from personal taxpayer's answer listed in KPP Pratama East Denpasar, which is answer to a series of questionnaires asked by researchers about factors that influence tax compliance. The sample was determined using nonprobability sampling with purposive sampling technique. The results of this study indicate that the implementation of e-Registration, e-Billing, and e-Filling positively affect the compliance of individual taxpayers at KPP Pratama East Denpasar Keywords: e-Registration, e-Billing,e-Filling, Personal Taxpayer Compliance